Long-term sequelae of coronavirus disease: long COVID-19 and cardiovascular outcomes (a literature review) - A. V. Hovornyan; T. O. Ilashchuk (Zaporožskij Medicinskij Žurnal)
The COVID-19 pandemic has serious global implications for the healthcare system and economy. Although the recovery rate has increased significantly and the morbidity rate has decreased, long-term consequences, particularly cardiovascular, have come to the fore and become a global problem. As a result, in 2021, at the WHO level, the concept of “long-term COVID” was introduced, including more than 100 already described symptoms in patients for at least 3 months after initial recovery. At the same time, the clinical symptoms are not specific, strategies for the treatment of such disorders have not been worked out, and measures to detect and/or prevent the development of these complications have not been organized.